Penerapan Teknologi Tepat Guna Pembuatan Biogas dari Kotoran Ternak Dalam Pendampingan Masyarakat Berkelanjutan Kelompok Tani Guo Mandiri di Kelurahan Kuranji Kota Padang - Herix Sonata MS; Wandy Lexmana; Mulyadi Mulyadi; Dewi Yudiana Shinta (PELANTAR PRESS, 2024)
The application of appropriate technology in making biogas from livestock manure is one solution to utilize livestock waste which is often a problem in the community. This article discusses the assistance of the Guo Mandiri farmer group in Kuranji Village, Padang City, in applying biogas technology as a sustainable alternative energy source. This mentoring activity includes education, technical training, to the installation and maintenance process of biogas units. The results show that biogas technology can reduce environmental pollution, reduce community dependence on fossil fuels, and provide additional economic benefits for farmer groups through the use of organic fertilizer produced from the biogas fermentation process. Through a participatory approach and support from various parties, the sustainability of this program is expected to become a model for other regions in the development of community-based renewable energy